THE AGRARIAN QUESTION, CLASS STRUGLE AND LABOR IN BRAZIL (CONTROVERSIAL AND NECESSARY DIALOGUE) - Thomaz Junior, Antonio [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
The agrarian question and the class struggle, located within the expressions of the work, enable us to understand how it is essential and necessary to prioritize the mechanisms of control and domination in our analysis. The tensions and controversies are at the heart of empowerment enlargement and / or legitimacy of class power, especially those who still invade public lands, reserves, protected areas, such as landowners, ranchers, iron foreheads of industrial / speculators, squatters etc., with the alliance of capital sectors (agribusiness, financial, fictitious, speculator, miner), which together protagonist the destructive development of capitalist productive forces. That's why, if we consider that the agrarian question includes not only productive aspects, based on production techniques, means of production, inputs, but also the land structure, land access mechanisms, private property, production circuits, distribution, circulation and final consumption, therefore, it is essential that we understand it as a living subject in our society, and that is nucleated within the class struggle.
Keywords: work; class struggle; agrarian question; territory